Gender gaps in Peruvian film audiovisual production. The experience of Lima producers - Eyzaguirre Flores, Sol María (2022)
This article analyzes the gender gaps in Peruvian cinematographic production and its professional, social, economic, and emotional effects on a group of women producers with five or more years of experience. Through semi-structured interviews, their carrier-long experiences are analyzed to identify how they perceive and deal with gender gaps in their daily lives. As a central result, we found that these gaps and social patterns are replicated in the field since the producers are aware of the existence of labor disparities and feminized tasks. However, this inequality is faced through democratization mechanisms such as gender quotas in work groups and the inclusion of more women in historically masculinized positions.